Spontaneous bilateral pneumothorax in a previously healthy COVID-19 patient: A case report - Haryati, Haryati; Nurrasyidah, Ira; Kusumawardhani, Erna (Indian Journal of Case Reports, 2024)
Coronavirus disease 2019 (COVID-19) is commonly linked with mild cough, fever, and shortness of breath symptoms. However, there have been reports of pneumothorax, which particularly occurred at least 1 week following symptom onset in elderly COVID-19 patients. Spontaneous pneumothorax (SP) is an uncommon but possibly fatal complication of COVID-19 pneumonia and is rarely reported in non-intubated patients. We report a case of a healthy, non-smoker 35-year-old young woman who presented with a 7-day cough, fever, and sudden shortness of breath. She was diagnosed with severe COVID-19 pneumonia, experienced a right SP, and developed a second pneumothorax on the contralateral side. She improved gradually following chest tube insertion in the right lung and conservative management for the left pneumothorax.